ANALISIS PENGARUH STRUKTUR MODAL TERHADAP PROFITABILITAS (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2018-2020) - Malik, Ernawati; Merliana Adsar, Wa Ode Silfi (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2023)
This study aims to determine and analyze the effect of capital structure (DER, DAR and CR) on profitability (ROE) in manufacturing companies engaged in the metals and similar sub-sectors listed on the IDX 2018-2020. In this study, secondary data is used in the form of annual financial statements of metal companies listed on the IDX for the 2018-2020 period obtained through the official website of the Indonesia Stock Exchange. In this study, the method used is descriptive analysis method and multiple linear regression analysis. Based on the research results, the following conclusions are obtained: 1) Capital structure as measured by the Debt to Equity Ratio (DER) has a significant effect on profitability as measured by Return on Equity (ROE) in a negative direction; 2) Capital structure as measured by Debt to Asset Ratio (DAR) has no significant effect on profitability as measured by Return on Equity (ROE) in a negative direction; 3) Capital structure as measured by Current Ratio (CR) has an effect on profitability as measured by Return on Equity (ROE) in a negative direction; 4) Capital structure as measured by Debt to Equity Ratio (DER), Debt to Asset Ratio (DAR), and Current Ratio (CR) simultaneously have a positive effect on profitability as measured by Return on Equity (ROE).